2008
DOI: 10.1002/j.2168-9830.2008.tb00957.x
|View full text |Cite
|
Sign up to set email alerts
|

A Theme‐Based Seminar on Environmental Sustainability Improves Participant Satisfaction in an Undergraduate Summer Research Program

Abstract: We analyzed seven years of pre-program and post-program survey data to evaluate the Clarkson University Research Experience for Undergraduates (REU) Site Program in Environmental Science and Engineering, and evaluated whether our program was successful at meeting the intended outcome of increasing participants' likelihood of attending graduate school and pursuing a career in science or engineering research or education. We also evaluated how participant satisfaction in the program changed with the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…In the context of the REU described by Grimberg, the students reported that the inclusion of the environmental sustainability theme made them more aware of the "value and greater context of their work." 13 Similarly, the REU being described in this paper emphasizes the creative process and its relationship with the scientific method as a broad theme of the program. To our knowledge, creativity has not been previously studied in the REU literature.…”
Section: Research Experience For Undergraduates (Reu) Programsmentioning
confidence: 95%
“…In the context of the REU described by Grimberg, the students reported that the inclusion of the environmental sustainability theme made them more aware of the "value and greater context of their work." 13 Similarly, the REU being described in this paper emphasizes the creative process and its relationship with the scientific method as a broad theme of the program. To our knowledge, creativity has not been previously studied in the REU literature.…”
Section: Research Experience For Undergraduates (Reu) Programsmentioning
confidence: 95%
“…One study shows that in addition to improving the relevancy of learning for all students, increasing contextual considerations may improve gender diversity in engineering [14]. In addition to project-based learning in the classroom, the contextrelevant nature of undergraduate research not only can allow students to develop a deep understanding of a technical topic or process, but also improve their research and professional skills [15]. It should be noted, however that these gains are relative to mentor involvement and effectiveness, and the nature of the work involved in the research: analyzing and evaluating data yields more gains than the act of following protocols [16].…”
Section: Context-based Learningmentioning
confidence: 99%
“…Accordingly, the well-known ABET engineering accreditation criteria 1 requires engineering graduates should be able to "design a system, component, or process to meet desired needs within realistic constraints such as economic, environmental, social, political, ethical, health and safety, manufacturability, and sustainability." Engineering educators have been making every effort to educate the future engineers in sustainability and to prepare them with solid knowledge to deal with the sustainability challenges [2][3][4][5][6] . The related topics have been taught both as core engineering and general education 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, in an educational institution, it could be implemented in four levels: university-level with a strategic plan, school-or college-levels, departmental-levels or individual-levels. Various pedagogies and approaches are used in teaching sustainability in different engineering disciplines, e.g., creating an interdisciplinary seminar as a summer research program 5 , or integrating sustainability into all engineering courses incrementally 6,7 , etc. In general, it is agreed that integrating sustainability into existing courses might be a better way 8,9 .…”
Section: Introductionmentioning
confidence: 99%